2021
DOI: 10.1021/acs.jmedchem.1c01539
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Next-Generation Tropomyosin Receptor Kinase Inhibitors for Combating Multiple Resistance Associated with Protein Mutation

Abstract: Tropomyosin receptor kinase (TRK) inhibition is an effective therapeutic approach for treatment of a variety of cancers. Despite the use of first-generation TRK inhibitor (TRKI) larotrectinib (1) resulting in significant therapeutic response in patients, acquired resistance develops invariably. The emergence of secondary mutations occurring at the solvent-front, xDFG, and gatekeeper regions of TRK represents a common mechanism for acquired resistance. However, xDFG mutations remain insensitive to second-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Due to the absence of crystal structures reported at present for TrkC mutants, the homology models of TrkC G623R and TrkC G696C were generated from TrkC wt (PDB: 6KZD). The TrkC G623R mutant is the substitution of the small glycine residue with an arginine-bearing additional bulky side chain, which causes the steric clash and directly interferes with larotrectinib and entrectinib binding to the protein. ,, Similarly, the TrkC G696C mutant is the substitution of the glycine residue G696 in the DFG motif with cysteine, which leads to steric hindrance between the thiol side chain of cysteine and the 2,5-difluorophenyl moiety of larotrectinib and compromises larotrectinib binding. , From the molecular docking, we found that the binding modes of TrkC wt and mutants with 11g were nearly identical. Most of the interactions observed are retained, and TrkC G623R or TrkC G696C mutants do not affect the binding modes (Figure C,D), which is consistent with the biological assay results that the type-I inhibitor larotrectinib lost potencies against TrkC G623R and TrkC G696C mutants when compared with 11g (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the absence of crystal structures reported at present for TrkC mutants, the homology models of TrkC G623R and TrkC G696C were generated from TrkC wt (PDB: 6KZD). The TrkC G623R mutant is the substitution of the small glycine residue with an arginine-bearing additional bulky side chain, which causes the steric clash and directly interferes with larotrectinib and entrectinib binding to the protein. ,, Similarly, the TrkC G696C mutant is the substitution of the glycine residue G696 in the DFG motif with cysteine, which leads to steric hindrance between the thiol side chain of cysteine and the 2,5-difluorophenyl moiety of larotrectinib and compromises larotrectinib binding. , From the molecular docking, we found that the binding modes of TrkC wt and mutants with 11g were nearly identical. Most of the interactions observed are retained, and TrkC G623R or TrkC G696C mutants do not affect the binding modes (Figure C,D), which is consistent with the biological assay results that the type-I inhibitor larotrectinib lost potencies against TrkC G623R and TrkC G696C mutants when compared with 11g (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The TrkC G623R mutant is the substitution of the small glycine residue with an arginine-bearing additional bulky side chain, which causes the steric clash and directly interferes with larotrectinib and entrectinib binding to the protein. 69,78,80 Similarly, the TrkC G696C mutant is the substitution of the glycine residue G696 in the DFG motif with cysteine, which leads to steric hindrance between the thiol side chain of cysteine and the 2,5-difluorophenyl moiety of larotrectinib and compromises larotrectinib binding. 78,80 From the molecular docking, we found that the binding modes of TrkC wt and mutants with 11g were nearly identical.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, resistance mediated by xDFG mutation remains a major challenge for next-generation TRK inhibitors. Though recent studies report that promising drug compounds designed to overcome multiple resistance possessed potent inhibitory activities to xDFG mutations as well as solvent-front and gatekeeper substitutions in vitro and in vivo ( 95 , 96 ), the exploration of new drugs to inhibit xDFG mutation is still facing unmet clinical needs.…”
Section: Trk Inhibitors and Resistancementioning
confidence: 99%
“…The in vitro metabolic stabilities of selected compounds were performed using human and rat liver microsomes in triplicate as described previously [ 50 ].…”
Section: Methodsmentioning
confidence: 99%